THE RELATIONSHIP BETWEEN FRIENDSHIP QUALITY AND SELF-ESTEEM AND LONELINESS IN LATE ADOLESCENCE - Siska Abbidah Kurniasari; Latifah Nur Ahyani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine the relationship between friendship quality and self-esteem and loneliness in late adolescence. This study uses a quantitative method with a correlational design. The sampling technique used is a sampling quota involving 200 final adolescents aged 18-21 years. The instruments used are friendship quality scales, self-esteem scales, and loneliness scales that have been tested for reliability. The results showed a significant negative relationship between friendship quality and loneliness with rxly -0.546 with p of 0.000 (p<0.01), and between self-esteem and loneliness with rxly -0.581 and p of 0.000 (p<0.01). These findings indicate that the higher the quality of friendship and self-esteem, the lower the tendency to be lonely in late adolescence. Therefore, improving the quality of friendship and self-esteem is very important to be considered as a preventive and intervention effort in reducing loneliness in this group.